Elucidating epigenetic mechanisms governing odontogenic differentiation in dental pulp stem cells: an in-depth exploration - Huang, Lei; Chen, Xuan; Yang, Xiaoxia; Zhang, Yinchun; Liang, Yiyun; Qiu, Xiaoling (Frontiers in Cell and Developmental Biology, 2024)
Epigenetics refers to the mechanisms such as DNA methylation and histone modification that influence gene expression without altering the DNA sequence. These epigenetic modifications can regulate gene transcription, splicing, and stability, thereby impacting cell differentiation, development, and disease occurrence. The formation of dentin is intrinsically linked to the odontogenic differentiation of dental pulp stem cells (DPSCs), which are recognized as the optimal cell source for dentin-pulp regeneration due to their varied odontogenic potential, strong proliferative and angiogenic characteristics, and ready accessibility Numerous studies have demonstrated the critical role of epigenetic regulation in DPSCs differentiation into specific cell types. This review thus provides a comprehensive review of the mechanisms by which epigenetic regulation controls the odontogenesis fate of DPSCs.